2017
DOI: 10.1038/s41598-017-03471-9
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and physiological responses to prey-related cues reflect higher competitiveness of invasive vs. native ladybirds

Abstract: Understanding the traits that might be linked with biological invasions represents a great challenge for preventing non-target effects on local biodiversity. In predatory insects, the ability to exploit habitats for oviposition and the physiological response to prey availability differs between species. Those species that respond more readily to environmental changes may confer to their offspring a competitive advantage over other species. Here, we tested the hypothesis that the invasive Harmonia axyridis (Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 58 publications
0
16
1
Order By: Relevance
“…When moving through the landscape, the ladybird female presumably explores reliable cues from suitable plant‐prey systems, as well as cues from other predatory insects (Obata, 1986; Agarwala et al, 2003; Alhmedi et al, 2010; Almohamad et al, 2010; Sloggett et al, 2011; Leroy et al, 2012a,b; Rondoni et al, 2017). Some of these signals are released over a longer distance, whereas others are deposited only on the patch.…”
Section: Discussionmentioning
confidence: 99%
“…When moving through the landscape, the ladybird female presumably explores reliable cues from suitable plant‐prey systems, as well as cues from other predatory insects (Obata, 1986; Agarwala et al, 2003; Alhmedi et al, 2010; Almohamad et al, 2010; Sloggett et al, 2011; Leroy et al, 2012a,b; Rondoni et al, 2017). Some of these signals are released over a longer distance, whereas others are deposited only on the patch.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural and electrophysiological experiments demonstrated that H. axyridis responds to volatile semiochemicals [ 1 , 31 , 32 ]. Additionally, various types of antennal chemoreceptor sensilla (notably basiconica, chaetica, and grooved peg) have been recently characterized [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because ladybird beetles have to deal with aphid colonies, which increase quickly but also quickly disappear from the agroecosystems, these predators are often forced to look for alternative preys to sustain their development 36 . In this scenario, some ladybird species might exhibit complex and unpredictable responses that confer them a competitive advantage over similar predators 37 . IGP, in particular, can foster the abundance of one ladybird species upon other predators 11 .…”
Section: Discussionmentioning
confidence: 99%